Synthesis, antimicrobial activity and molecular modeling study of some new pyrimidine derivatives - Al-Masoudi, Wasfi Abood; Mohmmed, Abeer Laily; Abass, Wamedh Hashim; Al-Masoudi, Najim Aboud (European Journal of Chemistry, 2015)
Condensation of 2-amino-4-chloro-6-methoxypyrimidine with aromatic aldehydes (2-hydroxy-1-naphthaldehyde, 3,4-dihydroxybenzaldehyde and piperonal) afforded products in good yields. The synthesized compounds (Schiff base of pyrimidine derivatives) were screened for their antibacterial activity against Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Klebsille, Pseudomonas aeruginosa and Salmonella. Additionally, the compounds were tested for antifungicidal activity against Candida albicans, Candida tropicalis and Aspergillus fumigatus. All compounds exhibited potent antibacterial and antifungal activity. Molecular modeling studies were performed, showing the hydrogen bindings and hydrophobic interactions.